The improvement of the on-time delivery for “company x” e-commerce orders during the golden quarter - Sukazi, Thobile Nomalungelo (University of the Witwatersrand, Johannesburg, 2024)
E-commerce has revolutionized global business and consumer interactions, offering convenience and accessibility across various domains like Business-to-Business (B2B), Business-to-Consumer (B2C), and Consumer-to-Consumer (C2C). The COVID-19 pandemic has accelerated digital transformation, with South Africa's e-commerce market showing robust growth projections, fuelled by factors such as improved internet penetration and shifting consumer behaviours. The Omni-channel strategy has become standard, with leading players leveraging digital capabilities to maintain market share. Notably, the "Golden Quarter" of retail, encompassing events like Black Friday and Singles Day, presents a pivotal opportunity for retailers to boost profits through strategic promotional efforts. As the market matures, focus shifts to optimizing the final mile of delivery, aiming to improve efficiency and reduce costs. This project seeks to explore tailored strategies for final mile optimization in Company X, aligning with the broader goal of enhancing efficiency and customer experiences in South Africa's growing e-commerce sector. Despite being the second-largest wholesale food distributor in South Africa, Company X experienced significant on-time delivery performance declines, particularly in its discount retailer brand, Banner 3. The analysis identified logistical bottlenecks in the final mile as the primary contributor to these challenges, resulting in an average delay of 4.3 days in the order fulfilment process. Additionally, the study highlighted the importance of addressing these challenges to maintain customer satisfaction, loyalty, and competitiveness in the rapidly evolving South African e-commerce landscape. This study employs a comprehensive framework and systematic approach to investigate the research questions and objectives. A qualitative research design involves one-on-one interviews conducted digitally via Microsoft Teams. Ethics clearance (MIAEC 099/23) was obtained, ensuring transparency and participant understanding. The sampling strategy prioritizes quality over quantity, with six diverse participants selected to provide rich qualitative data. Data analysis follows Braun and Clarke's thematic analysis approach, incorporating triangulation methods and emphasizing thorough documentation to ensure validity and reliability. This research has thoroughly investigated Company X's final mile delivery challenges during the Golden Quarter, providing comprehensive insights and recommendations for enhancement. Key findings underscore the significance of accurate forecasts, planning collaboration, proximity to customers, fleet and technology utilization, customer service levels, and delivery types in optimizing delivery performance. Recommendations encompass advanced forecasting models, collaborative planning efforts, tailored customer promises, technological enhancements, and automation to address identified challenges and capitalize on opportunities for improvement. The proposed strategies offer a strategic roadmap for Company X to enhance efficiency, customer satisfaction, and competitiveness in the e-commerce landscape, aligning with the study's objectives and concluding the project successfully. The tailored recommendations contribute valuable strategies for improving efficiency, customer satisfaction, and competitiveness. Future research could focus on evaluating the implementation of these strategies and exploring emerging technologies to further optimize the delivery process and adapt to evolving market dynamics.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Ecommerce; On-Time Delivery; SDG-9: Industry, innovation and infrastructure